Rapid Diagnosis of Bacteremia in Adults Using Acridine Orange Stained Buffy Coat Smears. (1990) - Miller, Mark; Mendelson, Jack
Abstract : The use of acridine orange stained buffy coat smears was assessed as a rapid screening test for bacteremia in adults. A total of 356 consecutive blood cultures were submitted with simultaneous anticoagulated blood samples, from which a buffy coat smear was prepared and stained with acridine orange (100 mg/L; pH 3.0). Forty-one of 356 blood samples (12%) yielded organisms in the blood culture system. Compared to blood culture, the overall sensitivity of acridine orange stained buffy coat smears was 16%, specificity 88%, and positive predictive value 13%. There was no statistically significant difference in performance of the test among patients who had fever greater than 39°C and/or shock. The low sensitivity and specificity of the test makes it unsuitable as a means of rapid screening for adults with suspected bacteremia.